ANALYSIS OF NEWMAN’S ERROR IN SOLVING PROBLEMS ON TWO VARIABLE LINEAR EQUATIONS MATERIAL BASED MATHEMATICAL CRITICAL THINKING ABILITY OF COGNITIVE STYLE AND STUDENTS’ HABITS OF MIND - Bangun Wicaksono; Hayatun Nufus; Hasanuddin (Jurnal Prinsip Pendidikan Matematika, 2021)
This research aimed at describing the kinds of student Newman’s error in solving problems based on mathematical critical thinking ability of cognitive style and habits of mind. This research was descriptive qualitative research using a case study design. The subjects of this research were 28 students of IX.2 grade at state junior high school 1 Pujud. Test, questionnaire, and interview techniques were used for collecting the data. The instruments used in this research were tests for mathematical critical thinking ability on quadratic functions material, GEFT, questionnaire for habits of mind, and interview. The data were analyzed by using reduction, presentation, conclusion, and verification. The findings of this research showed that 1) the students with FD and FI cognitive styles made errors in processing skills and writing the final answer. 2) The high HoM students made errors in processing skills and writing the final answer. The medium HoM students made errors in processing skills and writing the final answer. The low HoM students made errors in writing the final answers. 3) The high and low HoM of field independent students made errors in writing the final answer, The medium HoM of field independent students made errors in processing skill and writing the final answer, the high and medium HoM of field independent students made errors in processing skill and the low HoM of field independent students made errors in writing the final answer.